Maternal Bochdalek Hernia during Pregnancy: A Systematic Review of Case Reports - Jin-Young Choi; Song-Soo Yang; Jong-Hwa Lee; Hyun-Jin Roh; Jun-Woo Ahn; Jeong-Sook Kim; Soo-Jeong Lee; Sang-Hun Lee (Diagnostics, 2021)
Background: Since the first report of a diaphragmatic hernia from Ambroise Paré’s necropsy in 1610, the Bochdalek hernia (BH) of the congenital diaphragmatic hernia (CDH) has been the most common types with high morbidity and mortality in the neonatal period. Due to the nature of the disease, CDH associated with pregnancy is too infrequent to warrant reporting in the literature. Mortality of obstruction or strangulation is mostly due to failure to diagnose symptoms early. Data sources and study selection: A systematic literature search of maternal BH during pregnancy was conducted using the electronic databases (PubMed and EMBASE) from January 1941 to December 2020. Because of the rarity of the disease, this review included all primary studies, including case reports or case series that reported at least one case of maternal BH in pregnant. Searches, paper selection, and data extraction were conducted in duplicate. The analysis was performed narratively regardless of the control groups’ presence due to their rarity. Results: The search retrieved 3450 papers, 94 of which were deemed eligible and led to a total of 43 cases. Results of treatment showed 16 cases in delayed delivery after hernia surgery, 10 cases in simultaneous delivery with hernia surgery, 3 cases in non-surgical treatment, and 14 cases in hernia surgery after delivery. Of 16 cases with delayed delivery after hernia surgery, 13 (81%) cases had emergency surgery and three (19%) cases had surgery after expectant management. Meanwhile, 10 cases underwent simultaneous delivery with hernia surgery, 6 cases (60%) had emergent surgery, and 4 cases (40%) had delayed hernia surgery after expectant management. 3 cases underwent non-surgical treatment. In this review, the maternal death rate and fetal/neonatal loss rate from maternal BH was 5% (2/43) and 16% (7/43), respectively. The preterm birth rate has been reported in 35% (15/43) of maternal BH, resulting from maternal deaths in 13% (2/15) of cases and 6 fetal loss in 40% (6/15) of cases; 44% (19/43) of cases demonstrated signs of bowel obstruction, ischemia, or perforation of strangulated viscera in the operative field, resulting from maternal deaths in 11% (2/19) of cases and fetal-neonatal loss in 21% (4/19) of cases. Conclusion: Early diagnosis and surgical intervention are imperative, as a gangrenous or non-viable bowel resection significantly increases mortality. Therefore, multidisciplinary care should be required in maternal BH during pregnancies that undergo surgically repair, and individualized care allow for optimal results for the mother and fetus.